The Evaluation Of The Potential Of Tetrahydro-Β-Carboline Derivatives For The Treatment Of Addiction Using In-Vivo Model With Zebrafish And Using Liquid Chromatography-Tandem Mass Spectrometry For The Neurotransmitter Analysis - Mohamed, Siti Mazleena (2022)
Drug addiction treatment can include behavioural therapies, medications, or their combination. The available drug used in medication treatment is limited and has known side effects. The present study evaluates the addictive property of synthesized tetrahydro-β-carboline derivatives compounds since the previous study showed that the compounds positively impact analgesic activity. Forty-nine compounds have been screened for physicochemical properties before selecting further for in-vitro and in-vivo studies. Out of forty-nine compounds, fourteen compounds were chosen for in-vitro screening. Four compounds showed toxicity toward SK-N-SH cells, and two compounds were insoluble in the cell medium. Thus, only eight compounds proceeded for receptor functional activity through cAMP production. (6-methoxy-1,3,4,9-tetrahydro-2H-β-carbolin-2-yl)(phenyl)ethanone (OD1b) and 6-methoxy-2,3,4,9-tetrahydro-1H-β-carbolin-1-one (OD2a) showed the highest cAMP stimulation. Bioavailability radar for drug-likeness showed OD1b and OD2a located inside the optimal range suggesting good drug-like properties of the compounds. The rewarding effects of OD1b and OD2a were evaluated using the behavioural technique of conditioned place preference (CPP) using zebrafish as an animal model, and their neurotransmitters in the brain and body were measured.